2008
DOI: 10.1097/01.ccm.0000297161.41559.93
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilators in the management of acute heart failure

Abstract: Recent guidelines by the Heart Failure Society of America have recommended consideration for use of nitroprusside, nitroglycerin, or nesiritide in addition to diuretics to achieve hemodynamic and symptomatic improvement. This article reviews the results of previous studies evaluating the pharmacologic and clinical effects and safety profiles of these drugs in patients with heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 64 publications
0
38
0
1
Order By: Relevance
“…The clinical response to NTG is known to be highly variable between patients; this may be explained by vascular resistance to NTG in patients with heart failure. 6,18 Katz et al 19 reported a two-fold increase in femoral artery blood velocity after intra-arterial infusion of NTG in normal subjects. However, this response was markedly attenuated in patients with heart failure and could be overcome only by increasing the dose, suggesting vascular resistance to NTG in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical response to NTG is known to be highly variable between patients; this may be explained by vascular resistance to NTG in patients with heart failure. 6,18 Katz et al 19 reported a two-fold increase in femoral artery blood velocity after intra-arterial infusion of NTG in normal subjects. However, this response was markedly attenuated in patients with heart failure and could be overcome only by increasing the dose, suggesting vascular resistance to NTG in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports that vasodilators may decrease BNP (89); however, there is also the potential of increasing plasma renin level (89). The effect of NTG on coronary blood flow has not been investigated in ADHF but is known to increase coronary flow in other scenarios.…”
Section: Vasodilatormentioning
confidence: 99%
“…Nitrates may ameliorate the abnormal cardiovascular hemodynamics in ADHF by promoting vasodilation and consequently reducing ventricular filling pressure, systemic vascular resistance, pulmonary vascular resistance, and pulmonary capillary wedge pressure 3, 15. Additional benefits may be related to a reduction in subendocardial ischemia and mitral regurgitation 6. However, tachyphylaxis may develop and a constant dose of nitrates may fail to have a persistent effect, depending on the duration of use.…”
Section: Discussionmentioning
confidence: 99%